The Effect of Domestic Institutions on International Trade Flows: A sectoral analysis - Gert-Jan Linders (European Regional Science Association (ERSA), 2004)
Barriers to international trade are more sizeable than can be accounted for on the basis of formal trade barriers and transport costs alone. Search costs in the international marketplace and insecurity of property and contract enforcement have recently been stressed to explain this observation. This paper proposes that both elements can be combined to explain observed trade patterns. Distinguishing between homogeneous and differentiated product groups, we estimate gravity equations to investigate how patterns of bilateral trade are affected by variation in the quality of institutions across countries. JEL codes: F14, F15 Keywords: institutions, bilateral trade, gravity model, sectoral analysis, markets
Keywords: F14; F15; 330; institutions; bilateral trade; gravity model; sectoral analysis; markets